2020
DOI: 10.1186/s12883-019-1592-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of stroke and stroke related risk factors: a population based cross sectional survey in southwestern China

Abstract: Background: Stroke and its risk factors epidemiological survey can help identify individuals at higher risk and therefore promote stroke prevention strategies. The aim of this study was to estimate the current prevalence of stroke and high risk stroke population, and evaluate stroke associated risk factors in southwestern China. Methods: This was a multi-center, cross sectional survey in southwestern China from May 2015 to September 2015. The eight communities were selected at random, and 17,413 residents aged… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 36 publications
6
57
2
4
Order By: Relevance
“…The finding that 14.39% participants were at high risk for stroke in the current study was slightly lower than the 17.1% reported by Yi et al [ 10 ] in another large population-based study in southwestern China. This may be explained by the relatively younger age in the current study than Yi et al’s [ 10 ] study, as risk of stroke has been consistently shown to increase with aging [ 34 , 35 ].…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The finding that 14.39% participants were at high risk for stroke in the current study was slightly lower than the 17.1% reported by Yi et al [ 10 ] in another large population-based study in southwestern China. This may be explained by the relatively younger age in the current study than Yi et al’s [ 10 ] study, as risk of stroke has been consistently shown to increase with aging [ 34 , 35 ].…”
Section: Discussioncontrasting
confidence: 89%
“…The finding that 14.39% participants were at high risk for stroke in the current study was slightly lower than the 17.1% reported by Yi et al [ 10 ] in another large population-based study in southwestern China. This may be explained by the relatively younger age in the current study than Yi et al’s [ 10 ] study, as risk of stroke has been consistently shown to increase with aging [ 34 , 35 ]. However, when combining high-risk and middle-risk groups, over one third were at some risk of stroke, which is alarming and also consistent with the 2016 GBD study showing China has the highest age-standardized incidence of stroke in the world [ 3 ].…”
Section: Discussioncontrasting
confidence: 89%
“…In a multicenter cross-sectional survey from South western China, dyslipidemia was one of the stronger contributors for stroke. [ 21 ] However, in a national registry of hospitalized patient based data from the second largest city of Czech Republic hyperlipidemia showed 61% prevalence as a risk factor in ischemic stroke patients over a period of 1 year. [ 22 ] Higher prevalence of subtype hemorrhagic stroke with dyslipidemia was found as an incident finding in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of dyslipidemia varies widely according to the ethnic, socioeconomic and cultural characteristics of distinct population groups [ 12 ]. The level of serum lipids in the Chinese population has greatly increased since improved economic development was associated with changes in ways of life and food habits [ 13 ]. A survey in China showed that the geographical distribution characteristics of dyslipidemia was higher in north than in south, and higher in the coastal area than in the inland region [ 14 ].…”
Section: Discussionmentioning
confidence: 99%